The economic costs of weeds on productive land in New Zealand - J. T. Saunders; G. Greer; G. Bourdôt; C. Saunders; T. James; C. Rolando; J. Monge; M. S. Watt (International Journal of Agricultural Sustainability, 2017)
Here we review published research on the costs of weeds to New Zealand’s pastoral, arable and forestry sectors, and propose an alternative dynamic approach for future research. The studies reviewed had little in common methodologically, often contained guesswork, or were outdated. Their aggregation resulted in a conservative estimate of the cost of weeds to New Zealand’s agricultural economy of $1658 million (2014 NZD). To address deficiencies in previously used methodologies, a dynamic approach is developed and applied to a case study on giant buttercup in dairy pastures. This approach accounts for probable temporal changes in both the geographic extent of the weed and in producer prices and indicates annuitized costs (over the period 2012–2030) of $166 million, $259 million and $592 million for rates of spread of 144, 60 and 20 years for giant buttercup to invade all dairy regions in New Zealand. Comparing the aggregate cost of all weeds to the three productive sectors estimated from the historical data with these ‘dynamic’ estimates for the one species in dairy pasture, indicates that the historical data provide a substantial underestimate of the true aggregate cost of weeds to New Zealand’s agricultural economy.